Epidemic spread of OXA‐48 beta‐lactamase in Croatia. Issue 8 (August 2018) - Bedenić, Branka; Slade, Mia; Starčević, Lidija Zele; Sardelić, Sanda; Vranić‐Ladavac, Mirna; Benčić, Ana; Atalić, Vlasta Zujić; Bogdan, Maja; Bubonja‐Šonje, Marina; Tomić‐Paradžik, Maja; Tot, Tatjana; Lukić‐Grlić, Amarela; et al.
Abstract : Purpose. : A dramatic increase in OXA‐48 β‐lactamase was observed recently not only in large hospital centres, but also in smaller suburban hospital centres in geographic areas bordering Croatia. The aim of the study was to analyse the epidemiology, the mechanisms of antibiotic resistance and the routes of spread of OXA‐48 carbapenemase in Croatia. Methods. : Carbapenemase and other β‐lactamase and fluoroquinolone resistance genes were detected by PCR and sequencing. Whole‐genome sequencing (WGS) was performed on five representative isolates. The isolates were genotyped by PFGE. Results. : Forty‐eight isolates positive for OXA‐48, collected from seven hospital centres in Croatia from May 2016 to May 2017, were analysed (40 Klebsiella pneumoniae, 5 Enterobacter cloacae, 2 Escherichia coli and one Citrobacter freundii ). Thirty‐three isolates were ESBL positive and harboured group 1 CTX‐M 1 β‐lactamases. In addition to the β‐lactam resistance genes detected by PCR ( bla SHV‐1, bla OXA‐48 and bla OXA‐1 ), WGS of five representative isolates revealed the presence of genes encoding aminoglycoside resistance, aadA2 and aph3‐Ia, fluoroquinolone resistance determinants aac(6)Ib‐c, oqxA and oqxB, the sulfonamide resistance gene sul1, and fosA (fosfomycin resistance). IncL plasmid was found in all isolates. Two K. pneumoniae isolates belonged to ST16, two E. cloacae to ST66 and E. coli to ST354. K. pneumoniae isolates were allocated to five clusters by PFGE which occured in different hospitals, indicating epidemic spread. Conclusions. : The OXA‐48‐positive organisms found in this study showed wide variability in antibiotic susceptibility, β‐lactamase content and PFGE banding patterns. This study revealed a switch from the predominance of VIM‐1 in 2012–2013 to that of OXA‐48 in the 2015 to 2017.